Comparative Survival and the Cold-Induced Gene Expression of Pathogenic and Nonpathogenic Vibrio Parahaemolyticus from Tropical Eastern Oysters during Cold Storage - Francisco Alarcón Elvira (International Journal of Environmental Research and Public Health, 2020)
Expression of the regulatory stress rpoS gene controls the transcription of cspA genes, which are involved in survival and adaptation to low temperatures. The purpose of this study was to assess the growth kinetics of naturally occurring V. parahaemolyticus in shellstock oysters and in vitro and the cold-shock-induced expression of the rpoS and cspA gene response in vitro during postharvest refrigeration. Naturally contaminated eastern oysters (Crassostrea virginica) and pathogenic (Vp-tdh) and nonpathogenic (Vp-tlh) isolates were stored at 7 ± 1 °C for 168 h and 216 h, respectively. The regulatory stress (rpos) and cold-shock (cspA) gene expressions were determined by reverse transcription PCR. At 24 h, the (Vp-tdh) strain grew faster (p < 0.05) than the (Vp-tlh) strain in oysters (λ = 0.33, 0.39, respectively) and in vitro (λ = 0.89, 37.65, respectively), indicating a better adaptation to cold shock for the (Vp-tdh) strain in live oysters and in vitro. At 24 h, the (Vp-tdh) strain rpoS and cspA gene expressions were upregulated by 1.9 and 2.3-fold, respectively, but the (Vp-tlh) strain rpoS and cspA gene expressions were repressed and upregulated by −0.024 and 1.9-fold, respectively. The V. parahaemolyticus strains that were isolated from tropical oysters have adaptive expression changes to survive and grow at 7 °C, according to their virulence.